The Symbolism Of Malay Sufist Poet Ahmad Kamal Abdullah (Kemala) - Aishah Isahak; Rosni Samah (Usuli Faqih Research Centre PLT, 2024)
Al-Qanatir International Journal of Islamic Studies Volume 32 No.2 Page (277-293)